AN ANALYSIS OF THE USE OF SOCIO-AFFECTIVE STRATEGY IN TEACHING SPEAKING ENGLISH - Daniel Urslenton Wiser Sumang; Darmawan Darmawan; Maf'ulah Maf'ulah (e-Journal of ELTS (English Language Teaching Society), 2022)
This study was conducted through Library Research method which describes the implementation of socio-affective strategy in teaching speaking English. The aim of this study is to describe the steps on the implementation of socio-affective strategy to encourage students in teaching speaking English. The data sources were taken from scientific writing on the implementation of socio-affective strategy from 5 scientific writings. The results reveal that in using socio-affective strategies, the teacher or lectures used six steps of strategies such as reducing students’ anxiety, encouraging themselves to speak, controlling emotion, asking question, cooperating with others, and empathizing with others based on Oxford (1990). The students definitely have positive response toward the use of socio-affective strategy in teaching speaking English. They thought that socio-affective strategies is possible help them to enhance their ability, motivation, and confidence in speaking skill. It is concluded that using Socio-Affective Strategies in teaching speaking English is effective to increase students’ speaking skill. In other words, differences in the teaching procedures do not negatively impact the students speaking ability.the teaching procedures do not negatively impact the students speaking ability.